Pictures as a Media to Teach Descriptive Text - Jusak Kencana Sinuraya; Misrita Misrita; Indra Perdana (Edumaspul: Jurnal Pendidikan, 2024)
This research is focused to use a picture as a media to teach descriptive text to VIII graders at SMPN 4 Palangka Raya. This media aims to build the will of students to learn and help them to understand descriptive text, since English is hard subject to teach. Interesting media to attract students’ attention in teaching learning process is important, especially many students in SMPN 4 Palangka Raya find that English subject is hard and boring, they immediately lazy to study even just by listen to name of the subject, shows how essential to build a good atmosphere in the class. This research determined how using pictures as a media improve students in learning descriptive text. This research used one group pre-test and post-test pre-experimental design. This research instrument was a test and VIII grade students in SMPN 4 Palangka Raya as a subject. The mean score formula was implemented in this research to analyzing the data. The results showed that picture as a learning media is indeed affects students learning outcomes in terms of descriptive text. Researcher founds that picture as a media help teacher to increase students’ enthusiasm in learning, since it attracted students’ attention and make teaching learning process more interesting.